Efectos de seis sustratos, en Plantas de Melina (Gmelina Arbórea) para la producción en vivero, en la Zona de Babahoyo - Gonzabay Ramos, Jonathan Andrés (2016)
VIII. SUMARY Melina is one of the crops that currently has a high growth in the world and in the equator for its multiple use in industry and its economic and social importance. The present investigation was carried out in the experimental buildings "SAN PABLO", located at Km 7 ½ of the Babahoyo Montalvo road. The objective of this research was to evaluate the behavior and development of melina plants in the different substrates used with different proportions, in order to identify the suitable substrate for the production in nursery. The research was carried out in 6 treatments including a control with three replicates distributed In a randomized complete block design. For the evaluation of means the tukey test was used at 95% of probabilities, at 30, 60 and 90 days the plant height, leaf number, leaf length, leaf width, root length, and Stem diameter. The results obtained determined that the substrate of yellow soil 70% + soil to plant 30% obtained better results in 3 variables to study such as plant height, leaf width and stem diameter. While the soil substrate yellow 90% + 10% river sand showed the best results in two variables to study leaf number, leaf length these two substrates gave good results in the growth and development of melina.